Morphology Of The English Language And Its Functional Features - Uktamova, Mokhigul; Hakimjonova, Odinakhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis studies the theoretical foundations of the morphology of the English language and its functional features in the language system. The study defines the concept of morphology and analyzes the structure and classification of morphemes in the English language. Attention is paid to the processes of word formation, studying their role in expanding the lexical meaning. Grammatical forms are analyzed from the point of view of their functions in ensuring syntactic and semantic accuracy. The study presents linguistic examples illustrating morphological patterns in the English language. The results confirm the importance of morphological knowledge in the development of language competence.